Diagnostic accuracy of individual antenatal tools for prediction of small‐for‐gestational age at birth. (April 2017) - Poljak, B.; Agarwal, U.; Jackson, R.; Alfirevic, Z.; Sharp, A.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2017; 49: 433–434 ABSTRACT: Objective: To determine the accuracy of fetal and newborn growth charts for the prediction of small‐for‐gestational age (SGA) at birth (birth weight < 10 th centile). Methods: This was a prospective cohort study performed within a UK specialist fetal growth clinic. A total of 105 consecutive pregnant women referred for a suspected SGA fetus were included. All pregnancies were managed according to a standard protocol using estimated fetal weight (EFW) plotted on customized Gestation Related Optimal Weight (GROW) charts. The last antenatal estimates of EFW (according to charts of GROW, Hadlock et al . and Mikolajczyk et al .), abdominal circumference (AC) (according to charts of Hadlock et al ., INTERGROWTH‐21 st Project and Chitty et al .) or change in AC over time (calculated according to Pregnancy Outcome Prediction (POP) study) were compared against four birth‐weight charts (GROW, INTERGROWTH‐21 st, Mikolajczyk et al . and World Health Organization (WHO)). The ability of each antenatal test to predict adverse perinatal outcome (APO) was assessed. Results: Birth weight < 10 th centile was assigned in 62 (59%) neonates using the GROW chart, 57 (54%) using the Mikolajczyk et al. chart, 55 (52%) using the INTERGROWTH‐21 st chart and 51 (49%) using the WHO chart. AC‐Hadlock had the best negative likelihood ratio (range, 0.3–0.4) and sensitivity (range, 74%–82%) for predicting SGA as defined by all four postnatal birth‐weight charts. AC‐INTERGROWTH‐21 st had the best positive likelihood ratio (range, 5.9–10.9) and specificity (94%–96%). For prediction of APO, AC‐Hadlock and EFW‐GROW had the best sensitivities (57% and 52%, respectively), whereas AC‐POP had the best positive likelihood ratio (2.2) and specificity (88%). Antenatal prediction of APO increased to a sensitivity of 61% when AC‐POP and EFW‐GROW were combined; however, specificity was only 56%. Conclusions: We have identified wide variation in the diagnostic accuracy of various antenatal tools for the prediction of both SGA and APO, dependent on the choice of chart. Suboptimal diagnostic accuracy of commonly used antenatal tests may lead to increasing medicalization without prevention of APO. Researchers should focus their attention on a combination of fetal biometry and biomarkers for better prediction of SGA and prevention of APO. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.